KAJIAN KETERSEDIAAN LAHAN DITINJAU DARI RENCANA STRATEGIS PEN KAMPUS BERKELANJUTAN (STUDI KASUS DI BEBERAPA LOKASI KAMPUS FKIP UNS) - Sukatiman Sukatiman (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
The research purposed was  mapping campuses situations toward to sustainable strategic plan.  Kind of research is qualitative descriptive focused on specific targets. Its comprises of exsisting condition in 3 location campuses,  those were PTK Pabelan campus,  PGSD campus, and FKIP UNS Kentingan campus. The research showed that : 1) environment condition of three (3)location  campuses  had  sustainable infrastructure,  available  of  reforestasion,  and    cozy environment.  2)  PTK  Pabelan  and PGSD Laweyan  campuses had  available  open  space  suitable with regulation  of Public Works. 3) FKIP Kentingan  campus was over land used.